Synergistic effects of multiple enzymes from industrial Aspergillus niger strain O1 on starch saccharification - Wenzhu Guo; Jianhua Yang; Tianchen Huang; Dandan Liu; Qian Liu; Jingen Li; Wenliang Sun; Xingji Wang; Leilei Zhu; Chaoguang Tian (Biotechnology for Biofuels, 2021)
Abstract Background Starch is one of the most important renewable polysaccharides in nature for production of bio-ethanol. The starch saccharification step facilitates the depolymerization of starch to yield glucose for biofuels production. The filamentous fungus Aspergillus niger (A. niger) is the most used microbial cell factory for production of the commercial glucoamylase. However, the role of each component in glucoamylases cocktail of A. niger O1 for starch saccharification remains unclear except glucoamylase. Results In this study, we identified the key enzymes contributing to the starch saccharification process are glucoamylase, α-amylase and acid α-amylase out of 29 glycoside hydrolases from the 6-day fermentation products of A. niger O1. Through the synergistic study of the multienzymes for the starch saccharification in vitro, we found that increasing the amount of α-amylase by 5-10 times enhanced the efficiency of starch saccharification by 14.2-23.2%. Overexpression of acid α-amylase in strain O1 in vivo increased the total glucoamylase activity of O1 cultures by 15.0%. Conclusions Our study clarifies the synergistic effects among the components of glucoamylases cocktail, and provides an effective approach to optimize the profile of saccharifying enzymes of strain O1 for improving the total glucoamylase activity.